Spectroscopic evidence for intermediate species formed during aniline polymerization and polyaniline degradation - Planes, Gabriel Angel (2010)
Spectroscopic methods are used to investigate the formation of low molecular mass intermediates during aniline (ANI) oxidation and polyaniline (PANI) degradation. Studying ANI anodic oxidation by in situ Fourier transform infrared spectroscopy (FTIRS) it is possible to obtain, for the first time, spectroscopic evidence for ANI dimers produced by head-to-tail (4-aminodiphenylamine, 4ADA) and tail-to-tail (benzidine, BZ) coupling of ANI cation radicals. The 4ADA dimer is adsorbed on the electrode surface during polymerization, as proved by cyclic voltammetry of thin PANI films and its infrared spectrum. This method also allows, with the help of computational simulations, to assign characteristic vibration frequencies for the different oxidation states of PANI. The presence of 4ADA retained inside thin polymer layers is established too. On the other hand, FTIRS demonstrates that the electrochemically promoted degradation of PANI renders p-benzoquinone as its main product. This compound, retained inside the film, is apparent in the cyclic voltammogram in the same potential region previously observed for 4ADA dimer. Therefore, applying in situ FTIRS is possible to distinguish between different chemical species (4ADA or p-benzoquinone) which give rise to voltammetric peaks in the same potential region. Indophenol and CO2 are also detected by FTIRS during ANI oxidation and polymer degradation. The formation of CO2 during degradation is confirmed by differential electrochemical mass spectroscopy. To the best of our knowledge, this is the first evidence of the oxidation of a conducting polymer to CO2 by electrochemical means. The relevance of the production of different intermediate species towards PANI fabrication and applications is discussed. © the Owner Societies.